Renal Function Recovery after Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma - Lee, Byron H. (World J Urol, 2017)
PURPOSE: To understand the longitudinal renal function trends in patients undergoing radical nephroureterectomy (RNU) and identify clinicopathologic characteristics associated with estimated glomerular filtration rate (eGFR) recovery. METHODS: 147 patients were available for analysis. Longitudinal eGFR trends were assessed by plotting each patient’s eGFR measurements over time. The patient population was dichotomized using eGFR < 60 ml/min/1.73 m(2) versus ≥ 60 ml/min/1.73 m(2). Cumulative incidence and competing risk regression analysis were used to estimate recovery of postoperative eGFR to the preoperative level and identify clinicopathologic characteristics associated with eGFR recovery. RESULTS: Median age was 68.7 years and median preoperative eGFR was 55.9 ml/min/1.73 m(2). 63.6% were male and 95.8% were white. The cumulative incidence of eGFR recovery was significantly higher in patients with baseline eGFR < 60 ml/min/1.73 m(2) compared to those with baseline eGFR ≥ 60 ml/min/1.73 m(2) (p = 0.01), with recovery rates at 2 years of 56.6% vs. 27.7%, respectively. Multivariable analysis revealed that preoperative hydronephrosis (HR 1.80) and preoperative eGFR < 60 ml/min/1.73 m(2) (HR 1.87) were associated with increased chance of eGFR recovery. CONCLUSION: Over half of patients with preoperative eGFR < 60 ml/min/1.73 m(2) achieved eGFR recovery within the first three years after RNU, and hydronephrosis was a significant predictor of recovery. These findings should be considered when counseling patients regarding chronic kidney disease progression after RNU and timing of perioperative chemotherapy for high risk tumors.